Analisis Efektivitas Penerapan Sistem Digital terhadap Kenerja Usaha Mikro Kecil dan Menengah (UMKM) (Studi Kasus pada Usaha Rental Playstation Box (PlayBox) di Kota Medan) - Nurallikha Cinta Emdys; Anfas (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of digital system effectiveness on the business performance of PlayStation Box (PlayBox) rental enterprises that operate using a portable daily-rental system. The phenomenon of digitalization has encouraged traditional entertainment businesses to adapt by integrating digital technologies into their booking, payment, and customer management processes. This research employs a quantitative approach with a survey method targeting PlayStation rental operators who have implemented digital systems in their transactional and operational management activities. A saturated sampling technique was applied to 18 business owners (respondents) in Medan City. Data were analyzed using simple linear regression to measure the relationship between digital system effectiveness and business performance. The results indicate that the effectiveness of digital system implementation has a positive and significant effect on improving the performance of PlayBox rental businesses, particularly in terms of security, operational efficiency, service convenience, and market reach expansion. These findings highlight digitalization as a crucial factor in enhancing the competitiveness of rental-based entertainment businesses in the modern era. Optimization of digital systems and improved technological literacy are recommended to enable business owners to fully leverage digital opportunities.